Composite materials for transmission components reduce friction and wear. Issue 10 (October 2019) - Atkinson, Simon
Abstract : Freudenberg Sealing Technologies (FST) has spent several years developing special filler packages for new high-performance plastics materials that are targeted at applications such as sealing rings and thrust washers, which are used in automatic transmissions. This article briefly looks at these materials and describes the novel approach that the company is taking to the development of high-performance plastics.